Politeness Strategies on Students’ Responses to Teacher’s Online Announcements - Selgas, Genevieve S (International Journal of Social and Administrative Sciences, 2022)
The shift of the usual operations in education from face-to-face to distance learning due to the COVID-19 pandemic has made the Google classroom one of the online learning modalities. The study aims to identify the politeness strategies employed in students’ responses to the Bukidnon State University teachers’ Google classroom announcement within three semesters. It also explores the significant difference between genders in employing politeness strategies. The study applied a mixed-method research design. The findings show that the students employ four politeness strategies of Brown and Levinson (1987): Positive, Negative, Bald-On-Record, and Off-Record Strategies. In addition, the male students frequently use negative politeness strategies, which contradicts Lakoff (1975) claims that women’s language consists of hedges, apologies, and indirect requests, a negative politeness strategy. Thus, determining significant differences in politeness strategies among students needs other factors such as cultural differences, gender language, gender performativity, and teachers’ announcement to which the students respond.